(untitled) (Scientific journal of the Fergana State University, 2024)
This article analyzes the question of the views of our great compatriot Hakim at-Termizi on the problem of the inseparability of the human body (being) and spirit, human identity (nafs) in his scientific heritage. It also contains information about key concepts that occupy a special place in the moral views of Sufi scholars.